1993
DOI: 10.1073/pnas.90.4.1345
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and adaptation to dietary calcium and phosphate deficiencies increase intestinal plasma membrane calcium pump gene expression.

Abstract: The effect of vitamin D and other variables on the synthesis of the chicken intestinal plasma membrane calcium pump (PMCA) mRNA was assesed. The DNA probe for Northern analysis was obtained by reverse transcription and PCR with intestinal poly(A)+ RNA, using two 20-mer oligonucleotide primers homologous to the 3' coding region of the human teratoma PMCA. An EcoRI restriction fragent of the PCR product was cloned into the pBluescript I KS(-) phagemid vector, and the chimeric plasmid was used to transform Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(81 citation statements)
references
References 48 publications
(45 reference statements)
3
76
0
1
Order By: Relevance
“…Supporting results implying a reduction in the VDR mRNA levels in the CA1 and CA2 pyramidal cells of hippocampus in AD patients have been shown (Sutherland et al 1992). Vitamin D deficiency and/or VDR polymorphisms, which may decrease the affinity of VDR to vitamin D (Cai et al 1993;Bouillon et al 1998), may affect detoxification mechanisms, calcium homeostasis and expression of neurotrophins. This may lead to neuronal aging, neuronal damage and neurodegeneration via other genomic and environmental factors.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Supporting results implying a reduction in the VDR mRNA levels in the CA1 and CA2 pyramidal cells of hippocampus in AD patients have been shown (Sutherland et al 1992). Vitamin D deficiency and/or VDR polymorphisms, which may decrease the affinity of VDR to vitamin D (Cai et al 1993;Bouillon et al 1998), may affect detoxification mechanisms, calcium homeostasis and expression of neurotrophins. This may lead to neuronal aging, neuronal damage and neurodegeneration via other genomic and environmental factors.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, calcium homeostasis affects many cellular mechanisms, especially neurotransmission. Vitamin D was found to alter calcium uptake in some excitable cells by modulating the L-type voltage sensitive calcium channels in hippocampus and by inducing the synthesis of calcium binding proteins (Cai et al 1993;Landfield et al 1998;Garcion et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Schachter and colleagues (9) also found a transporter responsive to vitamin D. Others have reported that vitamin D stimulates the basal lateral membrane calcium ATPase believed to be a calcium transporter (10,11). These components have been put together in a diagrammatic fashion to present the current hypothesis of how 1,25-(OH) 2 D 3 stimulates active intestinal calcium absorption.…”
Section: Microarrays ͉ Trpv6 Ko Mice ͉ Vitamin D ͉ Vitamin D Mechanismentioning
confidence: 99%
“…The transepithelial calcium reabsorption depends on proteins that mediate the apical calcium entry within the cell, named TRPV5 and TRPV6 (transient receptor potential vanilloid channel), the diffusion of the ion throughout the cytoplasm bound to calcium-binding proteins (CaBP), such as CaBP-D9K or CaBP-D28K, and its extrusion to the extracellular environment in the basolateral membranes of the cells by the Na C /Ca 2C exchanger (NCX) or the plasma membrane calmodulin-dependent calcium ATPase (PMCA; Bindels et al 1991, Van Baal et al 1996, Hoenderop et al 2002, 2005, Bar 2009). This process is orchestrated by several hormones that regulate the expression and activity of the aforementioned proteins, including vitamin D3, androgens, and estrogens (Cai et al 1993, Hoenderop et al 2001, 2005, Van Abel et al 2002, Dick et al 2003, Meyer et al 2007, Oz et al 2007, Suzuki et al 2008, Hsu et al 2010, Yang et al 2011. Interestingly, the efferent ductules of roosters express high levels of vitamin D3 receptor (VDR), androgen receptor (AR), and estrogen receptors (ESR1 and ESR2 -also known as ERa and ERb respectively; Kwon et al 1997, Dornas et al 2007, 2008, Oliveira et al 2011a.…”
Section: Introductionmentioning
confidence: 99%